PERUSAKAN LINGKUNGAN SEBAGAI TINDAK PIDANA TERORISME - Kafrawi, Rachman Maulana (Faculty of Law, University of Muhammadiyah Malang, 2018)
This research aims to identify whether the environmental destruction could be considered as terrorism and to identify why the person who damaged the environmental should be considered as a terrorist. The conclusion of this research indicates a concept which views that the person who did enviromental destruction as terrorism. This concept is textual elaboration which is contained in section 10 Law No. 15, 2003 about the eradication of the terrorism. The crime for environmental destructions which are catagorized as terrorism are as follows: The impacts of the environmental destruction and pollution exceed Baku Mutu Lingkungan Hidup (BMLH), the poisonous chemicals release in the public areas (as happened during internal armed conflict in suriah on March 2011), there are bulk of victims, and it harms and damages the strategical vital objects. Based on those criterion, the environmental destruction is considered as equal as terrorism, because they are catagorized as a crime againts humanity. The environmental destruction happens because of low obedience and awareness of people to protect and to save the environment and it could be indicator that the law enforcement for environmental protection and management has not gone well yet. Based on this concept, it is expected that the responsibility and commitment of Indonesia could be achieved in order to ensure the protection and fulfillment of the environment and human rights and to reach the aims of environmental justice.